Effects of Self-efficacy Promotion on Swallowing Rehabilitation in Stroke Patient with Dysphagia: Case study - Lakrab, Chainarong; Bannaasan, Banyaporn; Sathiyamas, Jinpitcha (Thai Journal of Science and Technology, 2024)
One major issue that affects stroke patients is dysphagia. Patients thus heal more slowly. It plays a significant role in creating issues. including resulting in a low quality of life for the patient. Therefore, nurses are crucial in providing care for stroke patients in order to avoid dysphagia-related problems. It is critical that nurses support appropriate swallowing therapy using the right techniques. Before beginning to swallow, the patient’s readiness must be determined. consisting of the following: 1. Assessing awareness; 2. Evaluating verbal response; 3. Placing the patient in a high Fowler’s position (90 degrees); and 4. Conducting a swallowing test. Including strengthening the swallowing muscles as part of recovery. To encourage the mouth’s strength.